Kesalahan Penulisan pada Siswa Tingkat Dasar: Analisis Isi pada Karangan Siswa MI Nurul Falah OKI Sumsel - Tanenji Tanenji; Hani Atus Sholikhah (JIP Jurnal Ilmiah PGMI, 2017)
The objectives of the research were to find out and describe error analysis of student writing. This research was conducted using qualitative method with content analysis. The population of this research was the students of Madrasah Ibtidaiyah Nurul Falah Kutapandan Kecamatan Lempuing Kabupaten OKI Sumsel in the academic year 2015/2017. The data were obtained by the means of writing task. The result of the data analyses showed that eror analysis of student writings are (1) misordering, (2) misformating (3) additioni, and (3) omision.